2019
DOI: 10.1177/2325967119862503
|View full text |Cite
|
Sign up to set email alerts
|

Medical Supervision of High School Athletics in Chicago: A Follow-up Study

Abstract: Background: High school sports participation in the United States has increased dramatically over the past 25 years. A corresponding increase in the number of injuries has been noted, particularly in contact sports such as football. This has led medical and sports organizations nationwide to advocate for proper medical supervision of athletes at games and practices. Purpose: To gather information from Chicago public high schools to gauge how medical supervision for high school sports has changed in 2017 compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
(59 reference statements)
0
10
0
Order By: Relevance
“…Nine studies found that 48% -98% of schools had an AED on campus. [10][11][12][16][17][18][19]23,24 Tennessee had the lowest rate at 48%, while West Virginia high schools had the highest rate of 98% among the states included in the studies. 12,19 Four studies found that 61% -94.4% of schools had an AED available at all athletic venues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine studies found that 48% -98% of schools had an AED on campus. [10][11][12][16][17][18][19]23,24 Tennessee had the lowest rate at 48%, while West Virginia high schools had the highest rate of 98% among the states included in the studies. 12,19 Four studies found that 61% -94.4% of schools had an AED available at all athletic venues.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies aimed to identify if schools had adopted a formal EAP and demonstrated EAP adoption rates ranging from 55% -100% (Figure 2). [10][11][12][13][14][15][16][17][18] Figure 1. Flow diagram for study selection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Throughout the world, increasing numbers of adolescents participate in competitive sports, some of them with the ambition to become professional athletes or to qualify to the Olympic Games [ 5 ]. For instance, the past 25 years have in the U.S. seen an increase in student participation in high school athletics from 4 million participants 1971–1972 to 7.9 million in 2015–2016 [ 6 ]. Despite calls from the International Olympic Committee for more research [ 7 ], little is known about health service needs and use among adolescent competitive athletes [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%